Epidural butorphanol for post operative analgesia in lower limb surgeries: A comparative study with epidural tramadol - Deo, G P; Shrestha, S K; Shrestha, I N (Journal of Chitwan Medical College, 2017)
To compare the efficacy of epidural butorphanol and tramadol for post operative analgesia in lower limb surgeries. Randomized, controlled, double blind, prospective study conducted at Department of Anaesthesia and Critical Care, Chitwan Medical College from September 1st 2015 to August 31st 2016. 60 patients of ASA Grade I and II of either sex, aged between 18-65 years willing for epidural analgesia for post operative analgesia were included in the study. They were divided into two groups: Group B- Butorphanol group and Group T- Tramadol group. Subjects of Group B received 2mg of Butorphanol and 0.25% Bupivacaine making a total volume of 10 ml and that of Group T received 100mg of Tramadol and 0.25% Bupivacaine also making a total volume of 10 ml. Analgesic efficacy was assessed by Visual Analogue Scale (VAS). The onset and duration of analgesia along with side effects were also assessed. The quality of analgesia was studied using time to independent mobilization and overall patient satisfaction. Total number of patients was 60, of ASA Grade I and II, aged between 18-65 years. The mean age of patients in Group B was 42.6±11.7 years and 46.1±11.2 years in Group T. Time of onset of analgesia after epidural injection was 7.4±0.9 minutes in Group B and 12.7±1.5 minutes in Group T and the difference was found to be statistically significant. Duration of analgesia was 317.1±99.1 minutes and 438.8±136.6 minutes in Butorphanol and Tramadol groups respectively which was also statistically significant. Sedation was significantly higher in butorphanol group whereas nausea and vomiting was higher in tramadol group. Quality of analgesia in terms of patient satisfaction was better with epidural butorphanol. Both epidural tramadol and butorphanol were effective in relieving post operative pain however butorphanol had lesser side effects and greater patient satisfaction compared to tramadol but the duration of action was relatively short.